How Family and Health Cadres Enable Routine Integrated Antenatal Care (ANC) Attendance Among Pregnant Women: A Descriptive Phenomenological Study in Jombang, Indonesia - Ninik Azizah; Helmi Annuchasari; Vivin Eka Rahmawati; Dewi Triloka Wulandari (Utan Kayu Publishing, 2026)
Integrated Antenatal Care (ANC) depends on sustained attendance across pregnancy, yet routine participation remains uneven. This study explored how pregnant women interpret family and health cadre support for maintaining routine Integrated ANC at the Jarak Kulon Primary Health Care Center, Jombang. Routine was defined as attending scheduled Integrated ANC contacts (PHC/Posyandu) and rescheduling any missed appointment within the same month. Using descriptive phenomenology, purposive sampling recruited pregnant women residing in the catchment area who had attended Integrated ANC in the current pregnancy, along with health cadres and key family supporters. Data were collected in March 2025 through in-depth semi-structured interviews (10 pregnant women, 4 cadres, 3 family members), supported by participatory observation and document review, and analyzed iteratively using Miles and Huberman’s reduction–display–verification procedures with NVivo. Two interrelated themes were identified. Cadre support functioned mainly as informational and instrumental support—education on ANC and danger signs, schedule reminders (including WhatsApp), home follow-up after missed visits, and assistance navigating access constraints. Family support operated primarily as emotional and instrumental support—reassurance, accompaniment, financial prioritization, and household task adjustments that made attendance feasible. Overall, participants described support as strengthening confidence and capability to keep visits on schedule, consistent with House’s (1981) social support dimensions. Abstrak. Pelayanan Antenatal Terpadu (ANC) memerlukan kehadiran yang berkelanjutan sepanjang kehamilan, namun partisipasi rutin masih belum merata. Penelitian ini mengeksplorasi bagaimana ibu hamil memaknai dukungan keluarga dan kader kesehatan dalam mempertahankan kunjungan ANC Terpadu yang rutin di Puskesmas Jarak Kulon, Jombang. “Rutin” didefinisikan sebagai menghadiri kontak ANC Terpadu yang terjadwal (Puskesmas/Posyandu) dan menjadwalkan ulang setiap kunjungan yang terlewat dalam bulan yang sama. Dengan menggunakan fenomenologi deskriptif, teknik purposive sampling merekrut ibu hamil yang tinggal di wilayah kerja dan telah mengikuti ANC Terpadu pada kehamilan saat ini, serta kader kesehatan dan anggota keluarga pendukung utama. Data dikumpulkan pada Maret 2025 melalui wawancara mendalam semi-terstruktur (10 ibu hamil, 4 kader, 3 anggota keluarga), didukung observasi partisipatif dan telaah dokumen, lalu dianalisis secara iteratif menggunakan prosedur reduksi–penyajian–verifikasi Miles dan Huberman dengan NVivo. Ditemukan dua tema yang saling terkait. Dukungan kader terutama berfungsi sebagai dukungan informasional dan instrumental—edukasi tentang ANC dan tanda bahaya, pengingat jadwal (termasuk WhatsApp), tindak lanjut ke rumah setelah kunjungan terlewat, serta bantuan menavigasi kendala akses. Dukungan keluarga terutama berfungsi sebagai dukungan emosional dan instrumental—penguatan, pendampingan, prioritas pembiayaan, dan penyesuaian tugas rumah tangga sehingga kunjungan menjadi mungkin. Secara umum, partisipan memaknai dukungan sebagai penguat kepercayaan diri dan kemampuan untuk menjaga kunjungan tetap sesuai jadwal, selaras dengan dimensi dukungan sosial House (1981).